Clinical Outcomes of Critically Ill Patients Using Inhaled Nitric Oxide (iNO) during Intrahospital Transport - Leonid Koyfman; Omri Simchon; Anna Koyfman; Shoshana Mushaev; Benjamin F. Gruenbaum; Ron Gal; Michael Friger; Natan Arotsker; Alexander Zlotnik; Moti Klein; Evgeni Brotfain (Critical Care Research and Practice)
Critically ill patients with severe hypoxemia are often treated in the intensive care unit (ICU) with inhaled nitric oxide (iNO). These patients are at higher risk when they require intrahospital transportation. In this study, we collected clinical and laboratory data from 221 patients who were hospitalized in the general ICU and treated with iNO at Soroka Medical Center, Israel, between January 2010 and December 2019. We retrospectively compared the 65 patients who received iNO during intrahospital transportation to the 156 patients who received iNO without transportation. Among critically ill patients who were transported while being administered iNO, only one patient had an adverse event (atrial fibrillation) on transport. We found that maximal iNO dosage during ICU stay, duration of mechanical ventilation, and percent of vasopressor support were the only independent risk factors for ICU mortality in both study groups. No difference in primary outcome of ICU mortality rate was found between the critically ill patients treated with iNO during intrahospital transportation and those who were treated with iNO but not transported during the ICU stay. We anticipate that this study will advise clinical decision-making in the ICU, especially when treating patients who are administered iNO.